2016
DOI: 10.1136/bmjopen-2015-010335
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and its associated risk factors among urban school adolescents in Nepal: a cross-sectional study

Abstract: ObjectivesThe prevalence of non-communicable diseases is increasing in Nepal. Overweight and obesity are the major risk factors of many non-communicable diseases. Adolescence is a critical phase for development of overweight and obesity. Risk factors associated with overweight and obesity are not well understood in Nepal. The objective of the study was to identify the factors associated with overweight and obesity among adolescent students.SettingA cross-sectional descriptive study was carried out on higher se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
55
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 15 publications
17
55
6
2
Order By: Relevance
“…3, residing in the Hill region, were educated up to the primary level, and belonged to the richest wealth quintiles. All of these findings are consistent with previous studies conducted in Nepal and in neighboring India and Pakistan [14,38,39]. In general, the prevalence of overweight and obesity was found to be higher among urban women compared to rural women, which is also consistent with findings from earlier studies conducted in Nepal and other South Asian countries [16,36,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3, residing in the Hill region, were educated up to the primary level, and belonged to the richest wealth quintiles. All of these findings are consistent with previous studies conducted in Nepal and in neighboring India and Pakistan [14,38,39]. In general, the prevalence of overweight and obesity was found to be higher among urban women compared to rural women, which is also consistent with findings from earlier studies conducted in Nepal and other South Asian countries [16,36,21].…”
Section: Discussionsupporting
confidence: 92%
“…The current study found a positive association between watching television once a week and overweight and obesity among women of reproductive age, which is consistent with findings from Bangladesh and Myanmar [14,16]. A study of Nepalese adolescents found that watching television more than two hours per day increased the risk of becoming overweight by nine times compared to those who watched television less than two hours a day [39]. Similar associations were observed in Western countries, such as Australia and the United States [12,13], as well as in Asian countries, such as Iran and China [11,40].…”
Section: Discussionsupporting
confidence: 89%
“…This study is also consistent with another study conducted among higher secondary level adolescents with 5.8% overweight and 2.3% obese 9 . Similarly, this is also parallel with the fi ndings of another one study which showed the prevalence of overweight of 12.2% among adolescents 10. More than two third (75.0%) of the adolescents in this study were able to defi ne obesity correctly which is consistent with the fi ndings of the onestudy which showed 82.21% of students defi ned obesity correctly 11 . Likewise, in this study only 26.7% of the adolescents correctly mentioned the method of assessment of obesity using BMI.…”
Section: Discussionsupporting
confidence: 90%
“…The result was similar (65%) in a study conducted by Piryani et al in Nepal. 15 Higher purchasing power, higher socio-economic status and more exposure to unhealthy diet may be the contributing factors for respondents being more overweight/obese among private schools. In this study, the combined prevalence was higher among 16-17 years of age group and also it was observed as higher the age, higher was the BMI.…”
Section: Socio-demographic Factorsmentioning
confidence: 99%